Fluorescent In Situ Targeting Probes for Rapid Imaging of Ovarian‐Cancer‐Specific γ‐Glutamyltranspeptidase1. (4th May 2015) - Wang, Feiyi; Zhu, Ying; Zhou, Li; Pan, Liang; Cui, Zhifen; Fei, Qiang; Luo, Sihang; Pan, Dun; Huang, Qing; Wang, Rui; Zhao, Chunchang; Tian, He; et al.
Abstract γ‐Glutamyltranspeptidase (GGT) is a tumor biomarker that selectively catalyzes the cleavage of glutamate overexpressed on the plasma membrane of tumor cells. Here, we developed two novel fluorescent in situ targeting (FIST) probes that specifically target GGT in tumor cells, which comprise 1) a GGT‐specific substrate unit (GSH), and 2) a boron–dipyrromethene (BODIPY) moiety for fluorescent signalling. In the presence of GGT, sulfur‐substituted BODIPY was converted to amino‐substituted BODIPY, resulting in dramatic fluorescence variations. By exploiting this enzyme‐triggered photophysical property, we employed these FIST probes to monitor the GGT activity in living cells, which showed remarkable differentiation between ovarian cancer cells and normal cells. These probes represent two first‐generation chemodosimeters featuring enzyme‐mediated rapid, irreversible aromatic hydrocarbon transfer between the sulfur and nitrogen atoms accompanied by switching of photophysical properties.